Software de simulación ja titan en el aprendizaje de criterios económicos y practicar habilidades relacionadas con la toma de decisiones directas en los estudiantes de la UTC, de la carrera de ingeniería comercial en el periodo 2012-2013. - Aguilar Morales, Dario Javier (2015)
The objective of this research was to develop a teaching guide JA TITAN software for business decision making in students of the Technical University of Cotopaxi Commercial Engineering Career in the province of Cotopaxi., This project will provide the student with our university access to new technologies promoting the educational development of the campus. Using descriptive, explanatory and by applying the survey to students at the Technical University of Cotopaxi from the previous levels determined that 64% of students say they need a new system of learning as it is so necessary to handle a tool study generation technology while 36% have no interest in a simulator is implemented in college. The proposal is based on the development of the JA TITAN software manual, the virtual platform to help develop skills and abilities of decision making Marketing, Finance, Accounting, among others, by using knowledge acquired in classes taught in classrooms, providing students and teachers of different cycles, access to the use of new technologies.